Elevated nitrogen fertilization differentially affects jojoba wax phytochemicals, fatty acids and fatty alcohols - Tietel, Zipora; Melamed, Sarit; Galilov, Izabella; Ben-Gal, Alon; Dag, Arnon; Yermiyahu, Uri (Frontiers in Plant Science, 2024)
Jojoba wax is gaining popularity among cosmetics consumers for its skin wound healing and rejuvenation bioactivities, attributed to collagen and hyaluronic acid synthesis. However, information regarding wax phytochemical composition and quality parameters, as well as effect of cultivation practices, and fertilization in particular, on wax quality is limited. The aim of the current work was to study the effect of nitrogen (N) availability to jojoba plants on wax phytochemical composition and beneficial skin-related contents. For this, wax quality from a six-year fertilization experiment with five N application levels was evaluated. The chemical parameters included antioxidant activity, free fatty acid, total tocopherol, total phytosterol and oxidative stability, as well as fatty acid and fatty alcohol profile. Our results reveal that the majority of wax quality traits were affected by N fertilization level, either positively or negatively. Interestingly, while fatty acids were unaffected, fatty alcohol composition was significantly altered by N level. Additionally, fruit load also largely affected wax quality, and, due to jojoba’s biennial alternate bearing cycles, harvest year significantly affected all measured parameters. Results shed light on the effects of N application on various biochemical constituents of jojoba wax, and imply that N availability should be considered part of the entire agricultural management plan to enhance wax quality. Some traits are also suggested as possible chemical quality parameters for jojoba wax.